Immunologlubulin classes and nutritional factors in plasma and breast milk of lactating Mothers in Nigeria (2006)
Background: Breast milk is important for the overall well-being of infants. Although lactation is relatively robust in the face of poor nutrition, the implication of poor nutrition on non-nutritive factors in breast milk is inconclusive. Objective: This study was designed to find associations between nutritional and immune factors in maternal blood and breast milk with the aim to improve the needed public and individual strategies for a healthy infant. Method: A cross sectional study was conducted on 61 lactating Nigerian women aged 23-40years within the first 3 months postpartum. Anthropometric measurements were obtained while nutritional factors (total protein, albumin) and immunoglobulin classes (IgG, A and M) were estimated by Biuret, Bromocresol green and single radial immunodiffusion methods respectively in maternal plasma and breast milk. Results: Most (73.5%) of the lactating mothers had normal mean body mass index (i.e. not under weight nor obese) and the mean levels of plasma total protein, albumin, IgG, IgA and IgM were within normal reference ranges in these mothers. Nutritional and immunological indices increase in the plasma with length of lactation but decrease in breast milk with lactation. There were no correlation between BMI, plasma indices and milk indices in these lactating mothers. Conclusion: This study supports the superiority of colostrum over transitional or matured milk for the protection and nourishment of infants.